Cancer in pregnancy. (11th October 2018) - Botha, Matthys H.; Rajaram, Shalini; Karunaratne, Kanishka
Abstract: The incidence of cancer in pregnancy is increasing. The most frequent malignancies include breast and cervical cancers. Diagnosis may be complicated by late presentation. Imaging during pregnancy should consider risks to the fetus. Diagnostic work‐up, including tumor markers, can be influenced by the physiology of pregnancy. Treatment of cancer can often be safely administered with good maternal and fetal outcomes. Chemotherapy, radiotherapy, and surgery must be adapted to the pregnancy state. Counselling and emotional support are an essential part of management. Abstract : Diagnosis and treatment of cancer during pregnancy are challenging. Cancer can often be successfully managed throughout pregnancy without causing harm to the unborn baby.